PENGARUH PENAMBAHAN LIMBAH PERUSAHAAN DAERAH CANGKANG ALE-ALE, CANGKANG KERNEL, DAN LEM PLYWOOD TERHADAP KUAT TEKAN BETON - ‘Ain, Hurul (Civil Infrastructure Engineering and Architectural Design, 2020)
Ketapang regency is an area rich in marine natural resources and plantations. Ale – ale mussels are a potential marine natural resource whose capture produces negative impacts in the form of shell waste. And the natural resources of the plantations are oil palm which produces kernel shell waste and plywood wood companies which produce waste from machine glue. Where, these wastes have not been managed optimally. This is a challenge in research so that waste can be used as a mixture of concrete, has economic potential and reduces environmental impact. In this study, cylindrical samples with diameter (∅) 15 cm and height 30 cm. The percentage of waste is 30% of the weight of coarse aggregate. With a mixture ratio of 1 : 2 : 3 ( cement : fine aggregat, coarse aggregate ) with 3 samples from each type of waste to determine the compressive strength of 7, 14, and 28 days. The stages of implementation include the examination of material properties, sample making, weighing and the compressive strength test of the sample. The average compressive strength value of the 28-day age conversion obtained from the ale-ale shell waste test results was 177.64 kg / cm2, kernel shells amounted to 66.62 kg / cm2, and plywood glue amounted to 235.57 kg / cm2. Based on these data, plywood glue wastehas the highest compressive strength value.